Between the Sacred and the Profane: Notes on Portuguese Culture - Ribeiro, Orquídea Maria Moreira (2017)
Portuguese culture, among many aspects, is strongly marked by the period of maritime expansion and by the construction of the colonial empire, a time during which the profane-religious symbiosis manifests itself in all its civilizational splendor, visible in the material and immaterial heritage of Portuguese influence spread all over the world. As a result of a strategy that identifies the first structural decisions in the early fourteenth century with King D. Dinis, Portuguese imperial success fell victim to its own greatness and to the umbilical relationship between the Church and the political power, whose sins would be fatal and would facilitate a rapid decline dating back to the sixteenth century, whose causes and consequences were pointed out by contemporary voices. The Portuguese cultural features survived the empire and find their best expression in Brazil, an example of a cultural expression built of the sacred and the profane.